2008
DOI: 10.1111/j.1444-2906.2007.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between quality parameters and content of glycerol galactoside and porphyra-334 in dried laver nori Porphyra yezoensis

Abstract: Glycerol galactoside (GG; floridoside + isofloridoside) and porphyra-334 (P-334) are contained in nori (Susabinori Porphyra yezoensis and Asakusanori Porphyra tenera). Glycerol galactoside has been found to have bifidogenic growth stimulator activity and P-334 is known to have ultraviolet-absorbing activity in the UVA region of sunlight. These substances have, respectively, potential for application to pre-biotic foods and in cosmetics as a sunscreen. In the present study, to investigate the relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…However, the majority of the analysed samples range between 300 and 400 g kg −1 protein (Ishihara et al . ). An even higher protein content of 500 g kg −1 crude protein (CP) on a dry matter (DM) basis was reported by Noda ().…”
Section: Introductionmentioning
confidence: 97%
“…However, the majority of the analysed samples range between 300 and 400 g kg −1 protein (Ishihara et al . ). An even higher protein content of 500 g kg −1 crude protein (CP) on a dry matter (DM) basis was reported by Noda ().…”
Section: Introductionmentioning
confidence: 97%
“…The occurrence of color-faded nori is a heavy burden on the nori culture and processing industry. In our previous study, color-faded nori was found to contain over 10% GG by weight on a dry weight basis [9]. Although further human experiments are necessary to evaluate the prebiotic activity of GG in humans, we anticipate that the present data will contribute to the development of a new way of utilizing color-faded nori as a health-promoting foodstuff.…”
Section: Discussionmentioning
confidence: 90%
“…We recently found that color-faded nori contains large amounts of GG, more than 10% w/w in dry wt. [9]. In an in vitro study, we found that GG was a potential candidate for a prebiotic compound [10].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations